1997
DOI: 10.1016/s0031-9384(97)00249-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunity Costs and Behavioural Modulation in Male Laboratory Mice (Mus musculus) Exposed to the Odours of Females

Abstract: In a previous study, male laboratory mice experimentally immunodepressed with anti-thymocyte serum (ATS) showed changes in behaviour (aggression, general locomotory activity, and sleeping) and testosterone that are consistent with decision-making being modulated adaptively with respect to immunocompetence. We tested this idea further by repeating the experiment with the addition of female odours (soiled sawdust) to the home cages of males following ATS/control treatment. We predicted that, in the presence of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Following Barnard et al (1997a,b), we expected infected mice to downregulate testosterone and aggressive behaviour, but maintain or increase time spent sleeping, relative to controls, and for these di¡er-ences between infected and uninfected mice to disappear when animals were exposed to female odours. Although corticosterone has shown no evidence of modulation in relation to immuncompetence in our previous experiments (see Barnard et al 1996aBarnard et al , 1997aSmith et al 1996), glucocorticoids have an inhibitory e¡ect on the secretory function of Th2 cells which characterize the immune response to helminth infections generally (Grencis et al 1991;Finkelman et al 1995;Padgett et al 1995; but see Golding et al 1994) and are known to be e¡ective in protective immunity to H. polygyrus (Urban et al 1992). Some reduction in host-induced corticosterone levels might thus be expected among infected animals.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Following Barnard et al (1997a,b), we expected infected mice to downregulate testosterone and aggressive behaviour, but maintain or increase time spent sleeping, relative to controls, and for these di¡er-ences between infected and uninfected mice to disappear when animals were exposed to female odours. Although corticosterone has shown no evidence of modulation in relation to immuncompetence in our previous experiments (see Barnard et al 1996aBarnard et al , 1997aSmith et al 1996), glucocorticoids have an inhibitory e¡ect on the secretory function of Th2 cells which characterize the immune response to helminth infections generally (Grencis et al 1991;Finkelman et al 1995;Padgett et al 1995; but see Golding et al 1994) and are known to be e¡ective in protective immunity to H. polygyrus (Urban et al 1992). Some reduction in host-induced corticosterone levels might thus be expected among infected animals.…”
Section: Introductionmentioning
confidence: 81%
“…Moreover, the covariation can be manipulated predictably by increasing social stress or depressing immune function experimentally (Barnard et al 1996b(Barnard et al , 1997a.…”
Section: Introductionmentioning
confidence: 99%
“…This was to enable manageable sample sizes for individual observations both at pre-weaning and in subsequent phases. Male pups were chosen because previous work has shown important dominance-resistance trade-offs in male mice [36][37][38]. A total of 208 male pups from 52 females were included in the adult offspring stages of the experiment.…”
Section: Materials and Methods (A) Methods Overviewmentioning
confidence: 99%
“…In many species, trade-offs between survival and reproduction are manifest in impacts of changes in immunity on social and reproductive behaviour. There is a well-documented negative association between social dominance and disease resistance in mice [36][37][38]. Aggressive interactions among male mice determine social dominance, and hence access to mating opportunities, but increased aggression is costly and is associated with reduced resistance to disease.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on primer effects in male mice have been mainly investigated the hormonal changes of males triggered by female odors but only a few studies have been reported on the influence on sperm so far. For examples of the primer effects on hormones, it is known that female odors stimulate the release of LH (Maruniak and Bronson, 1976) and increase the level of plasma testosterone concentration (Barnard et al , 1997) in male mice. As for the primer effects on sperm, stimuli by female odors have been found to increase sperm density (Koyama and Kamimura, 2000) and the odors of adult males given to premature males are known to cause morphological abnormalities of spermatozoa (Aref'ev et al ., 1986).…”
Section: Introductionmentioning
confidence: 99%